Social Safety Theory: A Biologically Based Evolutionary Perspective on Life Stress, Health, and Behavior - Slavich, George M. (Annual Review of Clinical Psychology, 2020)
Social Safety Theory hypothesizes that developing and maintaining friendly social bonds is a fundamental organizing principle of human behavior and that threats to social safety are a critical feature of psychological stressors that increase risk for disease. Central to this formulation is the fact that the human brain and immune system are principally designed to keep the body biologically safe, which they do by continually monitoring and responding to social, physical, and microbial threats in the environment. Because situations involving social conflict, isolation, devaluation, rejection, and exclusion historically increased risk for physical injury and infection, anticipatory neural–immune reactivity to social threat was likely highly conserved. This neurocognitive and immunologic ability for humans to symbolically represent and respond to potentially dangerous social situations is ultimately critical for survival. When sustained, however, this multilevel biological threat response can increase individuals’ risk for viral infections and several inflammation-related disease conditions that dominate present-day morbidity and mortality.
Keywords: affiliation